(untitled) (Research, Society and Development, 2021)
This study evaluated the rate of per capita production of solid urban waste, as well as identified the main mechanisms for final disposal and treatment of solid urban waste collected from the state of Paraíba. In Brazil, the per capita production of solid urban waste is estimated at 1 kg. (hab.dia) -1, being produced around 210 thousand tons daily and collected on average 172 thousand tons daily. It was found that public cleaning services, in this state, of the amount of solid urban waste produced, are currently collected around 93% and of the fraction collected, 40% on average is being confined in landfills that are located in the region metropolitan area of the city of João Pessoa and in the city of Campina Grande. The estimated amount of solid urban waste collected daily is 2.600 tons.day-1, which corresponds to a quantity of putrescible organic matter of approximately 1.430.000 tons .day-1. Therefore, considering only this matrix of production of putrescible organic matter and that this organic matter will be used for the production of organic compost, a total of 858.0 tons of organic compost would be produced. day-1, which would provide an application of 15.9 tons of organic compost (ha.year) -1, in the potentially arable area. It can also be said that the containment of urban solid waste in a landfill is not safe in any respect, given the complexity of the containment process itself, the required area demand and associated financial costs, in addition to the by-products generated and the environmental impacts of the surroundings.